Effect of Celecoxib and Diclofenac on Blood Pressure, Renal Function and Vasoactive Prostanoids in Young Early Subjects - Sabeen Arjumand, Rafiah Hareem U Slam, Fouzia Perveen, Shahnaz Fatima, Liaqat Ali, Gul E Nazish, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Determination of celecoxib and diclofenac effects in early young subjects. Study design: Randomized study designed Methodology: All the participants received celecoxib 225 mg two times/day and diclofenac 80mg two times/day. First 21 days all participants received celecoxib treatment, before the start of the following medicine diclofenac 3.5 weeks gap was given. The blood pressure (BP) of patients was measured using the ambulatory blood pressure monitoring device (space labs model 90217A). Results: Group one consisted of young participants had a mean ± SD age 29 ± 3.4 while group 2 elderly had a mean ± SD age 55 ± 5.5. The mean body mass index was (group 1) 21.7 ± 1.8 kg/m2 and for group 2 = 27.3 ± 1.0 kg/m2. Group one had 5 (38.46%) females and 8 (61.53%) males while group 2 had 4 (30.76%) females and 9 (69.23%) males. The celecoxib medication baseline BP shows that there was no significant difference found in systolic blood pressure. Similar results for diastolic (mm Hg) for day and night time. Mean arterial pressure was higher in the elderly group -2 than in young group 1, Plasma renin activity was less in group 2 on day one compared to group 1. Plasma renin activity and concentration were decreased after 7 days of celecoxib and diclofenac treatment. A non-significant result was obtained. Group 1 Aldosterone serum (ng/l) for celecoxib received patients 11 ± 2.2 (ng/l) value for day one, day 7 = 13.2 ± 3.2, day 14 = 14.2 ± 3.4. Similarly in the case of diclofenac, the Aldosterone serum (ng/l) value for day one = 11.3 ± 21, day 7= 12.2 ± 2.3, and day 14 = 12.3 ± 2.1. A decrease in values was observed in both groups for aldosterone serum. For group-2 celecoxib, day one=15 ± 2.2, day 7= 14 ± 2.4*. day14= 14 ± 1.4. For diclofenac day one 15 ± 2.2, 7day= 15 ± 1.5, and 14 days = 14 ± 5.1. The comparison of both groups shows that the sodium and potassium decrease in both treatments in both groups. Conclusion: Overall, we got a non-significant response of both drugs on renal function and blood pressure. Keywords: blood pressure, renin angiotensin aldosterone system, non-steroidal anti-inflammatory drugs (NSAIDs)